Socialnomics how social media transforms the way we live and do business - Qualman, Erik 1972- (Hoboken, N.J. Wiley, 2011)
Welcome to the world of socialnomics, where consumers and the societies they create online have profound effects on our economy and the businesses that operate within it. Online word of mouth, social search, social commerce, and the influence of peer groups are making traditional marketing strategies obsolete. As a result, we no longer have a choice on whether we do social media; the question is how well we do it.
Introduction It's a people-driven economy, stupid -- Word of mouth goes world of mouth -- Social media = preventative behavior -- Social media = braggadocian behavior -- Obama's success driven by social media -- I care more about what my neighbor thinks than what Google thinks -- Death of social schizophrenia -- Winners and losers in a 140-character world -- Next steps for companies and the "glass house generation" -- Social media rolodex and resources -- Other insights and FAQs -- Socialnomics summary.
Includes bibliographical references (p. 283-291) and index.
Keywords: Internet marketing; Social media; Social networks; Electronic commerce